The Alteration of Circulating Lymphocyte Subsets During Tacrolimus Therapy in Neuromyelitis Optica Spectrum Disorder and Its Correlation With Clinical Outcomes - Wang, Liang; Huang, Wenjuan; ZhangBao, Jingzi; Chang, Xuechun; Tan, Hongmei; Zhou, Lei; Lu, Chuanzhen; Wang, Min; Lu, Jiahong; Zhao, Chongbo; Quan, Chao (Frontiers in Neurology, 2022)
Objectives We aimed to explore the alteration of circulating lymphocyte subsets before and after tacrolimus (TAC) therapy in neuromyelitis optica spectrum disorder (NMOSD) and its correlation with clinical outcomes. Methods Anti-aquaporin-4 antibody (AQP4-ab)-positive patients with NMOSD treated with TAC were followed and clinically evaluated at 0, 3, 6, and 12 months after initiation of TAC. Flow cytometry was employed to detect the proportion of various whole blood lymphocyte subsets at every time point. Correlation analysis was further performed to explore the association between annualized relapse rate (ARR), the Expanded Disability Status Scale (EDSS) score, and the proportion of circulating lymphocyte subsets before and after TAC therapy. Results A total of 13 eligible patients with NMOSD were included. The proportion of CD19+CD24hiCD38hi/CD19+ and CD19+CD5+CD1dhi/CD19+ lymphocyte subsets increased significantly after TAC therapy (p = 0.010 and p < 0.001). The proportion of CD19+BAFFR+, CD19+IFN-γ+, and CD19+IL-10+ subsets decreased significantly after TAC therapy (p = 0.015, 0.018, and 0.042, respectively). There was a negative correlation between CD4+CD25hi subset and EDSS score (p = 0.016, r = −0.652). Conclusion Possibly through increasing regulatory B and suppressing BAFFR+ B and interferon (IFN)-γ+ B subsets, TAC could decrease relapse. EDSS score may be correlated with some lymphocyte subsets after TAC therapy.